TYPES OF FEEDBACK USED BY THE STUDENTS IN INTERMEDIATE WRITING CLASS - Hendra Alamsyah; Rina Listia; Fatchul Mu'in (Jurnal Bahasa Lingua Scientia, 2021)
Writing is the most complicated skill among other language skills. In the writing activity, the students have to invent ideas and organize them into sentences and paragraphs that will be clear for readers. Feedback is crucial to give significant improvement to student's writings. Peers and maybe various can provide feedback. This study's objective was to describe the types of feedback used by students of the Intermediate Writing Class in writing an argumentative paragraph. Descriptive qualitative was the design of research. The subjects of this research are A1 and A4 Intermediate Writing course students of the English language Education Study Program of Lambung Mangkurat University. The data were collected through observation and document analysis. The data were then analyzed through three steps: familiarizing and organizing, coding, and interpreting and representing. The result was found that the students used several feedback types, namely written feedback as responding and written feedback as correcting. Written feedback as correcting used by the students consists of direct feedback, metalinguistic feedback, and unfocused feedback. From some of the metalinguistic feedback that some students used, they were using the grammatical description. Some of the metalinguistic feedback that some students used was the metalinguistic explanation (grammatical description). There was no metalinguistic feedback of the error code. There was only one student who used unfocused feedback. In conclusion, the students used four feedback types: written feedback as responding, written feedback as correcting, or written corrective feedback consisting of direct feedback, metalinguistic feedback, and unfocused feedback. Written feedback as responding is the feedback that the students used most while doing peer feedback. The students need to look for more information and explanation or feedback from the teachers and their friends and give feedback while doing peer feedback properly to not only use one type of feedback.